Effects of Methanol Extract of Breadfruit (Artocarpus altilis) on Atherogenic Indices and Redox Status of Cellular System of Hypercholesterolemic Male Rats - Oluwatosin Adekunle Adaramoye; Olubukola Oyebimpe Akanni (Hindawi Limited, 2014)
We investigated the effects of methanol extract of Artocarpus altilis (AA) on atherogenic indices and redox status of cellular system of rats fed with dietary cholesterol while Questran (QUE) served as standard. Biochemical indices such as total cholesterol (TC), triglycerides (TG), low- and high-density lipoproteins-cholesterol (LDL-C and HDL-C), aspartate and alanine aminotransferases (AST and ALT), lactate dehydrogenase (LDH), reduced glutathione, glutathione-s-transferase, glutathione peroxidase (GPx), catalase (CAT), superoxide dismutase (SOD), and lipid peroxidation (LPO) were assessed. Hypercholesterolemic (HC) rats had significantly increased relative weight of liver and heart. Dietary cholesterol caused a significant increase (P<0.05) in the levels of serum, hepatic, and cardiac TC by 110%, 70%, and 85%, LDL-C by 79%, 82%, and 176%, and TG by 68%, 96%, and 62%, respectively. Treatment with AA significantly reduced the relative weight of the organs and lipid parameters. There were beneficial increases in serum and cardiac HDL-C levels in HC rats treated with AA. In HC rats, serum LDH, ALT, and AST activities and levels of LPO were increased, whereas hepatic and cardiac SOD, CAT, and GPx were reduced. All biochemical and histological alterations were ameliorated upon treatment with AA. Extract of AA had protective effects against dietary cholesterol-induced hypercholesterolemia.